The rise and fall of serum theophylline concentration: a comparison of sustained-release formulations in volunteers with rapid theophylline clearance. - Mucklow, J C (1985)
The pharmacokinetics of four sustained-release formulations of theophylline have been examined after single doses (Nuelin SA, Phyllocontin, Slo-phyllin and Theo-Dur) and at steady-state (Phyllocontin, Theo-Dur) in six healthy adult volunteers, selected because they all eliminated theophylline rapidly after an intravenous dose of aminophylline. After a single dose of Theo-Dur, the peak concentration of theophylline was smaller and occurred later than after single doses of Nuelin SA, Phyllocontin and Slo-phyllin, suggesting that absorption occurs over a longer period. The systemic availability of theophylline was virtually complete after all four formulations. After repeated 12-hourly dosing to steady-state, and adjustment of dose to achieve trough concentrations of between 5 and 10 mg l-1 (28-55 mumol l-1), theophylline concentration fluctuated to a significantly greater extent within a dose interval when the subjects were taking Phyllocontin than when they were taking Theo-Dur.